ELECTROCHEMICAL SYNTHEZIS AND CHARACTERIZATION OF POLYPYRROLE FOR DODECYLSULFATE SENSOR MEMBRANE - Abdul Haris Watoni; Suryo Gandasasmita; Indra Noviandri; Buchari Buchari (Indonesian Journal of Chemistry, 2007)
A conducting polymer, polypyrrole, has been electrochemically synthesized from pyrrole monomer using cyclic voltammetry technique in aqueous solution in the presence of HDS dopant and KNO3 supporting electrolyte. The polymer was deposited on the surface of an Au-wire and the modified electrode obtained was then used as dodecylsulfate (DS-) ion sensor electrode. The best performance PPy-DS modified-Au electrode conditioned in the air system without HDS or SDS solution gave linear potential response for the concentration range of 1.0 x 10-5 - 1.0 x 10-3 M, sensitivity of 54.5 mV/decade, detection limit of 1.0 x 10-5 M, and response time of 23 - 30 second.  The electrode showed good selectivity towards other anions, therefore can be used to determine SDS concentration in real samples system without any change of the samples matrix.